ANALYSIS OF FISHERIES POLICY TO IMPROVE REGIONAL DEVELOPMENT FOR IMPLEMENTING DECENTRALIZATION IN THE POST TERRITORIAL PROLIFERATION IN MOROTAI ISLAND DISTRICT PROVINCE NORTH MOLUCAS - Muhammad Fitrawan Popa; Sutiyo Sutiyo; Widodo Sigit Pudjianto (Jurnal Scientia, 2023)
This study aims to analyze the fisheries potential to increase the Regional Development of Morotai Island Regency in the context of implementing regional autonomy after the proliferation of the area, to analyze what constraints are obstacles in developing fisheries potential to increase the Regional Development of Morotai Island Regency. This study uses a descriptive qualitative research method. Sources of data are primary data and secondary data. Data collection techniques include observation, interviews and documentory study. Methods of data analysis with data reduction, data presentation, and concluding. The results of this study show that fisheries policy has had a positive effect on implementing post-expansion decentralization in Morotai Island District. The synergy of the central and regional governments also creates an investment climate for investors for the fishing industry, existing regulations can be a reference in creating healthy activities for the development of fisheries policies in Morotai Island Regency, contributing to increasing local economic activity, employment, and the growth of the industry in the fishing industry area,the model of the fishing industry in Morotai Island Regency is determined by 4 (four) main aspects, including: aspects of Marine and Fisheries Resources management (SDKP) which include optimization of SDKP management and calculation of economic valuation of SDKP sustainability, aspects of economic development and business, which includes supply chain efficiency, sector contributions, and business or investment financing needs,aspects of community development which include the social relations of business actors and the role of managing actors; and regulatory aspects of the fishing industry development program in Morotai Island Regency. The economic integration strategy focuses on implementing the fishing industry model as the basis for producing and exporting fresh tuna. Its implementation is the synergy and commitment of regional leaders to carry out the program sustainablyto achieve the goals. Although sectoral, the implemented programs, require synergy and coordination between relevant stakeholders. The local government must optimize the potential of tuna resources in the Morotai region so that it becomes a source of regional income. Meanwhile, optimization of fisheries can be focused as a center for tuna production and marketing.